Cystic hemangioblastoma in a pregnant Patient: A case report - Jhoel Garcia-Bohorquez; Nelson Cuevas; Laura Aristizabal-Perez; Henry Garcia-Vargas; Jhon Comba; Diego Muñoz-Suarez; Sergio Torres-Bayona (Interdisciplinary Neurosurgery, 2024)
Introduction:  Brain tumors in pregnancy are a pathology that implies risk for both maternal and fetal health, currently there is no guideline regarding the indications for surgical management in this group of patients; therefore, it is considered a case of interest. Case Report: We describe the case of a 39-year-old female patient who was diagnosed with a posterior fossa cystic hemangioblastoma during her 19-week pregnancy. In view of this imaging finding and the clinical presentation, in conjunction with maternal fetal medicine, it was decided to perform a suboccipital craniectomy to remove the lesion. Histopathology and immunohistochemistry were compatible with a hemangioblastoma. Postoperative evolution was satisfactory, and the patient was discharged from the hospital 5 days after surgery. Conclusions: The presence of a brain tumor associated with pregnancy implies a high risk of maternal and perinatal morbidity and mortality, requiring multidisciplinary management and a treatment team with surgical experience.